Analysis of Online Transportation Service Applications Selection Using Analytical Hierarchy Process (AHP) Method - Abizar Al Ghiffari, Hadraji Mufti; Refika Cyntia Sari; Popy Ridhona Tambunan; Pundari Zuhayka; Muhammad Syahru Ramadhana (Bulletin of Islamic Economics, 2025)
This study aims to analyze user preferences in choosing online transportation service applications using the Analytical Hierarchy Process (AHP) method. The study was conducted by distributing questionnaires to 51 respondents from various regions in Indonesia, who are active users of Gojek, Grab, and Maxim applications. Four main criteria were used as the basis for evaluation, namely service speed, price, promotion, and driver availability. The results of data processing show that service speed is the most dominant factor in decision making with a weight of 51%, followed by driver availability (23%), promotion (15%), and price (11%). Of the three applications studied, Gojek obtained the highest priority value (0.47), making it the top choice of respondents. This research shows that operational aspects such as speed and service availability are more decisive than price considerations alone, and confirms the relevance of the AHP method in assisting complex, user preference-based decision making.